Ethnomathematical perspectives on Galah Asin: Investigating the mathematical and cultural significance of a traditional game - Deda, Yohanis Ndapa; Rosa, Milton; Disnawati, Hermina; Tamur, Maximus (Jurnal Elemen, 2024)
Traditional game (TG) Galah Asin has been played for generations—a game cultivated from generation to generation for Timor Tengah Selatan residents, Indonesia-Timor Leste Border Area. People must be aware that Galah Asin's TG and activities contain mathematics concepts that can be employed in math study. This study examines ethnomathematics in Galah Asin, a conventional game in Mnelalete Village, West Amanuban District, South Central Timor Regency, NTT Province, Indonesia. An ethnographic approach was used to investigate the data. Ethnomathematics emphasizes understanding a culture's concepts, methods, and practices from its members' perspectives. The study collects data through observation, interviews, and documentation. This study analyzed data using taxonomy, domain, componential, and cultural theme analysis. The study results found flat, translational, reflecting, line, angel, and congruence geometry ideas in the game arena, body movement, and player position of Galah Asin. Galah Asin also has addition, subtraction, multiplication, and division in gameplay. The implication of exploring ethnomathematics study is that understanding cultural activities can be integrated into school mathematics instruction. In addition, the ethnomathematics exploration of TG impacts the preservation of local culture.